EMPLOYEE DATA MINING BASED ON TEXT AND IMAGE PROCESSING. - Prof. Vijay .More; Ms. Ankita Shetty; Ms. Aishwarya Mapara; Mr. Rahul Ghuge; Mr. Rohit Sharma (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Employees of any company need to know whether their employees are happy or sad or they have any problem in their working environment. There should be some mechanism to handle this information about the employee. Employee chatting messages could be analyzed using sentiment analysis and employee mood detection is retrieved based on text analysis. Also, Employee facial expressions can be detected using Image Processing on employee images taken through Web Camera while an employee is chatting with colleagues. Using Image Processing, Emotion of employee such as Happy, Angry, Sad or Normal is detected. Employee analysis report is shown to company management to find whether the employee is satisfied with company or employee is facing some problem in the working environment.